Career information, career counseling, and career development - Brown, Duane (b, 2016)
"For those pre- and in-service school counselors, life coaches, and others preparing to do career counseling in schools. A comprehensive, authoritative look at the day-to-day, nuts and bolts responsibilities of the career counselor, from a global perspective. This extensive revision of the highly popular text known and appreciated for its strong focus on the practical, day-to-day tasks and responsibilities of the career counselor looks at careers from a global perspective, or a one-world economy approach to the issues. In it, theory integrates with practice through the use of case studies and examples that bring the concepts to life. Written by a leading expert in the field, Career Information, Career Counseling and Career Development allows students to sample the broad array of career options available to them, understand and deal effectively with the rapid changes in technology and how those changes can be used to foster career development and contribute to the assessment process, understand more fully the relationship of theory and practice, and relate more sensitively with clients regarding their age, gender, race, ethnic group, or sexual orientation."--Publisher's description
Includes bibliographical references and index.
Keywords: Vocational guidance -- Information services; Vocational guidance -- Bibliography